The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/ef501242k
|View full text |Cite
|
Sign up to set email alerts
|

Structural Comparison of Asphaltenes of Different Origins Using Multi-stage Tandem Mass Spectrometry

Abstract: In this work, six petroleum asphaltene samples of different geographical origins were studied using atmospheric pressure chemical ionization (APCI) in positive ion mode in a linear quadrupole ion trap mass spectrometer (LQIT). APCI doped with carbon disulfide reagent was selected as the ionization method as it has been previously demonstrated to generate stable molecular ions with no fragmentation for asphaltene molecules. The mass spectra measured using this approach revealed the apparent molecular weights (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 49 publications
2
63
2
Order By: Relevance
“…Similar results were observed for model compounds as well as asphaltenes by using mass spectrometry with collision-induced dissociation (CID) fragmentation, which results in an average number of 3-8 fused rings with up to 20 carbon atoms in alkyl-side chains. [19,[28][29][30] Nonetheless, although the island model serves to describe some asphaltene properties, such as reservoir geodynamics, it is incongruent with asphaltene behavior in several scenarios, e.g., products observed after thermal upgrading or pyrolytic degradation. After thermal cracking, the newly formed maltene fraction has been found to consist of alkylated 1-5-ring aromatics, alkanes, and alkenes, as well as naphthenes.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were observed for model compounds as well as asphaltenes by using mass spectrometry with collision-induced dissociation (CID) fragmentation, which results in an average number of 3-8 fused rings with up to 20 carbon atoms in alkyl-side chains. [19,[28][29][30] Nonetheless, although the island model serves to describe some asphaltene properties, such as reservoir geodynamics, it is incongruent with asphaltene behavior in several scenarios, e.g., products observed after thermal upgrading or pyrolytic degradation. After thermal cracking, the newly formed maltene fraction has been found to consist of alkylated 1-5-ring aromatics, alkanes, and alkenes, as well as naphthenes.…”
Section: Introductionmentioning
confidence: 99%
“…2 with a single polycyclic aromatic hydrocarbon (PAH) per molecule previously proposed by time resolved fluorescence polarization studies [24][25] has been confirmed by laser desorption, laser ionization mass spectrometry (L 2 MS). [26][27] Further evidence for 1.5 nm asphaltene structures has been observed in tandem mass spectrometry coupled with collisional activation decomposition, 28 in interfacial studies at an oil-water interface, [29][30][31] and in sum-frequency generation experiments. 32 2.0 nm nanoaggregates of about seven molecules have also been confirmed by SALDI-MS. 26,33 These weakly bound nanoaggregates are readily disrupted.…”
Section: Flory-huggins-zuo Model For Asphaltene Equilibrium Distributmentioning
confidence: 89%
“…Figure 1 depicts the asphaltene molecular representations obtained from the stochastic algorithm, with their corresponding molecular weights and the fraction they have in the mixture. These representations were generated from the experimental data of Maya crude oil [20], [21]. It is worth noting that all four molecules, as individuals, as well as the pondered average of the set, are within the accepted criteria for the asphaltene structural description [22].…”
Section: Modelmentioning
confidence: 99%